Understanding the Factors Lead to the Adoption of Content Localization Strategy by OTTP in India: A Review - Navami P; Thomas, Dr. P.E (International Journal of Scientific Research and Management (IJSRM), 2022)
OTT, the new video streaming service in India has rapidly evolved over the last few years. Post Covid era forced the people to follow a new and different pattern of video consumption which accelerated the growth of OTT platforms. Unlike traditional TV, in the new platform content creators can communicate with their consumers directly through an internet interface which offers much ease viewing at one’s own convenient space and time. Changing demographics, growing internet penetration & data consumption, affordable smart phones, elevated the trend and later leads to cord-cutting phenomenon. However a close analysis of OTT platform shows that apart from the demographic and infrastructural changes success of the new video platform is primarily determined by the quality and variety of content delivered by the OTT media. To compete with the traditional TV and the emerging regional OTT platforms, content strategists adopt different innovative idea. This report is the overview of the factors that leads to the adoption of the content localization strategy by OTTP in India. The study also entails the opportunity of particular strategy.